KEDUDUKAN HARATO PUSAKO TINGGI SETELAH PUNAHNYA SUATU KAUM (KAJIAN PADA SUKU KUTIANYIR DATUAK MAJO ITAM KENAGARIAN TUJUAH KOTO TALAGO KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA) - Robby Yunianto Utama MS (Ensiklopedia Research and Community Service Review, 2026)
This research is backgrounded by the phenomenon of clan extinction at the paruik (matrilineal branch) level in the Minangkabau matrilineal kinship system, which often triggers disputes and deviations in the transfer of harato pusako tinggi (high ancestral property) rights. This study aims to determine the legal status of harato pusako tinggi after a clan's extinction and to identify the rightful heirs. This study employs a juridical-sociological approach with a descriptive qualitative method. Data were collected through in-depth interviews with customary leaders, members of the Village Customary Council (KAN), and related parties in Nagari Tujuah Koto Talago, along with library research. The results indicate that: (1) The status of harato pusako tinggi in the Kutianyir Datuak Majo Itam tribe remains as collective property of the clan and does not downgrade to pusako randah (low ancestral property) or personal property, even when its management is transferred to other branches through the ganggam bauntuak system, in accordance with the customary principle of kabau tagak kubangan tingga. (2) The right to inherit and manage the property belongs to the barih or bloodline heirs (warih nasab) who have the closest kinship within the same tribe (sajari, sajongka, saheto, sadapo), while non-bloodline heirs (warih badan) have no rights unless based on a strong customary consensus. This study concludes that local customary law successfully maintains the existence of high ancestral property against deviant property transfers.Keywords: Harato Pusako Tinggi, Clan Extinction, and Minangkabau Customary Law